Antagonism of carbenicillin and cefamandole by cefoxitin in treatment of experimental infections in mice. - Goering, R V (1982)
The ability of cefoxitin to antagonize the in vivo efficacy of cefamandole and carbenicillin as predicted by in vitro assays was analyzed in experimental infections in mice. Cefoxitin was administered in a nonprotective dose either at the time of challenge or simultaneously with the protective drug, 1 and 3.5 h postchallenge. In mice infected with Enterobacter cloacae, median 50% protective doses of cefamandole and carbenicillin were markedly increased by cefoxitin, especially when the latter was given at the time of challenge. The antagonistic effect was also associated with increased numbers of challenge bacteria present in animal heart blood within a 6.5-h period after infection. In infections with Pseudomonas aeruginosa, cefoxitin antagonized carbenicillin; however, the effect was less dramatic than that seen with E. cloacae. Antagonism in this model was pronounced with simultaneous administration of antagonizing and protective drugs. The antagonistic effects observed in all in vivo tests were not due to the selection of stable resistance to the protective drugs, but appeared to be due to a reversible induction of beta-lactamases by cefoxitin.